2009
DOI: 10.1063/1.3271827
|View full text |Cite
|
Sign up to set email alerts
|

Relation between critical current of domain wall motion and wire dimension in perpendicularly magnetized Co/Ni nanowires

Abstract: We investigated the relation between critical current of domain wall motion and wire dimension by using perpendicularly magnetized Co/Ni nanowires with different widths and thicknesses. The critical current, Ic, became less than 0.2 mA when w<100 nm, suggesting that magnetic random access memory with domain wall motion can replace conventional embedded memories. In addition, in agreement with theory, the critical current density, jc, decreased as wire width decreased and became much less than 5×107 A/cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 25 publications
1
33
0
Order By: Relevance
“…Using FeNi nanowire, racetrack memory has been proposed [6] and demonstrated the accurate operation. Then several experiments have been conducted, Jc value was successfully reduced to 3 Â 10 7 A/cm 2 by using a perpendicular magnetized Co/Ni nanowire [7][8][9]. As a reason of Jc reduction, it was considered that DW motion of Co/Ni nanowire is due to only intrinsic pinning effect [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Using FeNi nanowire, racetrack memory has been proposed [6] and demonstrated the accurate operation. Then several experiments have been conducted, Jc value was successfully reduced to 3 Â 10 7 A/cm 2 by using a perpendicular magnetized Co/Ni nanowire [7][8][9]. As a reason of Jc reduction, it was considered that DW motion of Co/Ni nanowire is due to only intrinsic pinning effect [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, an increasing number of experimental investigations of the DW motion in nanowire with perpendicular magnetic anisotropy ͑PMA͒ have been reported [4][5][6][7][8][9][10][11] because experimental as well as theoretical studies revealed that nanowires with PMA required much less current density to propagate the DW than ones with in-plane magnetic anisotropy. [12][13][14][15] However, only a few PMA materials such as Pt/ Co/ AlO x , 6 Co/Ni, [8][9][10][11] and ͑Ga,Mn͒As 12 have been shown to support steady DW motion induced by a pure electric current and further investigation on other possible materials is demanded. In this study, we focused on the use of a perpendicularly magnetized CoFeB/MgO nanowire as a DW-motion material.…”
mentioning
confidence: 99%
“…Subsequently, it was theoretically predicted that by using perpendicular-easy-axis systems with a reduced wire thickness, the hard-axis anisotropy, which governs J th in the adiabatic regime becomes so small that a DW can be moved by the adiabatic STT at a reasonably small current density. 66,67) Following the theoretical prediction, experimental studies using a perpendicular-easy-axis Co=Ni multilayer demonstrated DW motion driven with a small current density, [68][69][70][71] as explained well by the adiabatic-STT model. 71) In this system, the independence between J th and H C was also confirmed.…”
Section: Structure and Characteristics Of Three-terminal Spintronics mentioning
confidence: 99%